Hubungan Kebiasaan Sarapan, Aktivitas Fisik, Kualitas Tidur dengan Konsentrasi Belajar pada Siswa/I Kelas X dan XI di Wilayah Kecamatan Bogor Utara - Ratna Sari Ramdani; Gusti Kumala Dewi (Lembaga Pengembangan Kinerja Dosen, 2026)
Cognitive concentration constitutes a pivotal determinant within the educational process; when an individual exhibits impaired attentional capacity, the instructional input received is unlikely to be effectively encoded into neural pathways or long-term memory, thereby rendering the expenditure of effort, time, and resources essentially futile. This investigation sought to elucidate the associative dynamics among breakfast consumption patterns, levels of physical activity, and sleep quality in relation to academic concentration among students in Grades X and XI within the North Bogor District. Employing a cross-sectional methodological framework, the study encompassed 101 participants whose selection adhered to an observational analytic approach. Empirical data pertaining to breakfast behavior, physical activity, sleep quality, and concentration performance were acquired through standardized self-administered questionnaires. Analytical procedures were conducted using the chi-square statistical test. The inferential findings demonstrated a statistically significant association between breakfast habits (p = 0.002) and sleep quality (p = 0.008) with learning concentration, whereas physical activity exhibited no significant correlation (p = 0.831). Accordingly, the study substantiates that breakfast regularity and sleep quality are meaningfully interrelated with students’ concentration levels, while physical activity does not manifest a measurable relationship with concentration outcomes